THE USE OF MONOPOLY GAME AS A TEACHING MEDIA TO ENHANCE STUDENTS’ ABILITY IN PRESENT CONTINUOUS TENSE (A Classroom Action Research at the Eighth Grade of SMP Katolik Unggulan Santa Maria Timika) - Ria Miftachul Faidah; Deasy Natalia Lessu; Ridwan Nur (Universitas Labuhanbatu, 2022)
Grammar is the basic knowledge of language to understand English perfectly. Some students who study English face difficulties in understanding grammar, especially in mastering present continuous tense. The teacher must find new techniques to improve the students' mastery in grammar. Monopoly game is one of the techniques used to assist students in mastering present continuous tense. The aim of this research was to find out the implementation of Monopoly Game as teaching media in improving the students’ ability in learning present continuous tense. Method: This research applied classroom action research to collect the data, which was carried out through four steps. They were planning, action, observation, and reflection. The subjects of this study were 31 students at the eighth grade of SMP Katolik Unggulan Santa Maria Timika in the academic year of 2022/2023. The research findings showed that there was a development on the students’ ability in present continuous tense. It was proven by the mean score of pre-test was 28, the mean score of post-test in the cycle I was 50, and the mean score of post-test in the cycle II was 72. The percentage of the students’ score in the pre-test was 3,2%, and the percentage of the students’ score in the post test of the cycle I improved into 32%. It means that there was improvement as much as 28,8%. Then, the percentage of the students’ score in the post test of the cycle II was 77%. It means that the improvement was 73,8%. From the data above, it is indicated that using Monopoly Game as teaching media in learning present continuous tense was effective. It can be concluded that the students’ ability in present continuous tense had been improved by using Monopoly Game as the teaching media